Quantified Desistance: A Scoping Review of Conventions in the Scientific Literature - Leclair, Marichelle (Crime & delinquency, 2022)
This paper adopts a conventionalist approach to shed light on the measurement and reification problems that underlie the quantification of desistance from crime in the scientific literature. Analysis of 100 papers spanning three decades indicates that approaches based on theoretical classification have recently lost ground in favor of more sophisticated techniques aimed at empirically identifying subgroups. These techniques convey the impression of objectiveness among statistics users and consumers and, as a result, the classification ?desisters? and ?persisters? are increasingly reified. Findings suggest that the quantification of desistance is intimately linked to the maintenance of a classification system that constitutes delinquency as a stable category and contributes to ?making? up new kinds of people over which institutions can legitimately intervene.